ATTITUDINAL MEANINGS IN BILINGUAL TRAVEL ARTICLES: A CASE STUDY - Dalilah Fathma; Harni Kartika Ningsih (Masyarakat Linguistik Indonesia, 2022)
Translating travel article texts requires a consideration of the way the tourist destinations are promoted. This ‘promotional’ element of travel articles, an inseparable part of the text type, is significant to inform translation practices. However, studies in this area are quite lacking in that the element is not well-understood, i.e. how ‘promotion’ can be identified in both the source and target texts and if there are potential changes between the texts. This paper compares the construction of promotion in bilingual tourism texts published in an in-flight magazine as a case study. This is done by examining the attitudinal meanings in the source text (ST), written in Indonesian, and the target text (TT) in English. It uses the interpersonal system of appraisal proposed by Martin and White from systemic functional linguistics to analyse the construal of affect, appreciation and judgement in the promoted items found in the texts. The genre stages and register were also identified to situate the context. Keywords: travel article, appraisal, attitude framework.